Reconfiguring globalisation: A review of tariffs, industrial policies, and the global solar PV supply chain - Linxiao Zhu (The Oxford Institute for Energy Studies, 2024)
Trade barriers have become an increasingly popular policy design for protecting and nurturing domestic clean-tech manufacturing industries in major economies, including the US, EU, Canada, and India. Confronted with a surge of Chinese solar photovoltaics (PV) imports at drastically reduced prices, a consequence of China's rapid manufacturing expansion, multiple countries are poised to launch or strengthen existing trade barriers. However, despite extensive discussion within policy and industry circles, the effectiveness and broader impact of such policies remain underexplored in the existing literature. This paper attempts to address this gap by exploring the role of trade barriers as major economies grapple with the dilemma between decarbonisation and de-risking from Chinese equipment critical for the energy transition. This paper begins by analysing the trade conflicts of the early 2010s and their impact on the US, EU, and Chinese industries, as well as on the global supply chain. It then explores how recent and impending trade conflicts - along with the rise of green industrial policies aimed at promoting import substitution - are reshaping the global supply chain by assessing both government policies and corporate responses. Lastly, the paper examines policy solutions for the rest of the world (ROW), considering trade actions and industrial policies in the context of China's overcapacity in 2024.
Keywords: 330; China; de-risking; industrial policy; IRA; overcapacity; reshoring; solar PV; Subsidy; Supply Chain; Tariff; Trade